Agua - Trumbauer, Lisa, 1963-; Ramos, Gloria (Bloomington, Minn. : Red Brick Learning : Capstone Press, 2006)
Decribes the different forms that water can take.
Includes index.
Translation of: Water.
Text in Spanish.
Keywords: Water -- Juvenile literature; Spanish language -- Texts -- Juvenile literature